A New Reading: The Rediscovery of Myth in Existential Fantasy Literature Foments a War of Worldviews (KULT_online, 2009)
Christian Kölzer’s dissertation Fairy tales are more than true uses two popular trilogies to demonstrate the basic principles of mythic and neo-mythic world interpretation in modern fantasy literature. With a text-immanent approach of J. R. R. Tolkiens The Lord of the Rings and Philip Pullmans His Dark Materials Kölzer proposes a genre of "existential Fantasy Literature". In his opinion, this genre should be received as the "heiress of the classical myth" (p. 7). Even for those unfamiliar with the primary literature, Kölzer's theories and analyses of religious and literary studies are readily accessible. Referring to this new reading as a rediscovery of the myth, Kölzer’s study provides an auspicious entry into the research of fantasy literature.